Menggugat Tradisi Talak Muslim Lombok: Upaya Mengawal Hak-hak Perempuan - abdullah abdullah (Universitas Islam Negeri (UIN) Mataram, 2020)
The purpose of this study was to examine the talak tradition that developed in the Lombok Muslim community in Gunungsari Subdistrict, the focus of the problem in this study was the fulfillment of rights. Because the meeting of Islamic law with the local custom of the community causes the color of the living law to vary. In this study, researchers used a qualitative approach to data collection using observation and interview methods. This research found several Muslim chili talak traditions. First, reporting men to religious and community leaders about the divorce. Second, pecelekan (Returning the bride to her parents' house). Third, nullifying the husband's obligation (aborting the rights of the wife) in living expenses for clothing and food. From these traditions, there are traditions that need to be maintained because many bring benefit, while other traditions must be eliminated because they conflict with the Qur'an and are detrimental to women